Challenges in editing late nineteenth-and early twentieth-century prose fiction: what is editorial “completeness”? - Guy, Josephine; Scott, Rebekah; Conklin, Kathy; Carrol, Gareth (ELT Press, 2016)
Guy, Scott, Conklin, and Carrol join forces to analyze controversial questions about multi-volume variorum editions of late nineteenth- and early twentieth-century writers such as Wilde, Conrad, Woolf, James, and Wyndam Lewis. What prompted such ambitious, costly editions that take years to complete? How do editors plan to compete with the many popular and scholarly editions readily available? Controversy has also emerged about the readership for these projects and how editorial principles have changed. At center is the thorny question of the role of an editor's value judgments and the "completeness" of an edition. On what grounds can a variorum edition claim to be "definitive"? Is there a better means of determining the "meaningfulness" of textual variants than a reliance on editorial judgment alone? Guy and company offer a timely consideration of variorum editions, the kinds of textual data such editorial scholarship provides and its relevance to literary critical judgments.